Periungual capillaroscopy in psoriasis Capilaroscopia periungueal em psoríase - Camila Ferrari Ribeiro; Elisa Beatriz Dalledone Siqueira; Ana Paula Holler; Lincoln Fabrício; Thelma Larocca Skare (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Nailfold capillaroscopy is a useful technique for evaluating changes in microcirculation. OBJECTIVE: To investigate changes at nailfold capillaroscopy in psoriatic patients compared with controls. METHODS: Nailfold capillaroscopy was performed in 46 psoriatic patients and 50 controls to assess microscopic morphological changes, capillary density and the presence of areas with devascularization. RESULTS: Patients with psoriasis had lower capillary density (p=0.0005), increased avascular areas (p=0.0035) and an increased number of morphologically abnormal capillaries (coiled, p<0.0001) compared to controls. No association was found between capillary density and the duration of the disease (p = 0.92) or the extent of skin involvement, as measured by the psoriasis area and severity index (PASI) score (p = 0.59). The presence of avascular areas was more common in psoriatic individuals whose nails were affected by the condition (p = 0.047). CONCLUSION: Patients with psoriasis have decreased capillary density and a greater presence of morphologically abnormal capillaries when compared to controls. FUNDAMENTOS: A capilaroscopia periungueal é um método utilizado no estudo de alterações da microcirculação. OBJETIVO: Verificar alterações na capilaroscopia periungueal de pacientes com psoríase, comparando-os com controles saudáveis. MÉTODOS: A capilaroscopia periungueal foi realizada em 46 pacientes com psoríase e 50 controles, utilizando-se um estereomicroscópio e observando-se alterações morfológicas, densidade capilar e presença de áreas com desvascularização. RESULTADOS: Pacientes com psoríase tinham menor densidade capilar (p=0,0005), maior presença de áreas avasculares (p=0,0035) e de capilares morfologicamente alterados (enrodilhados; p<0.0001) do que os controles. Não se encontrou associação entre densidade capilar e tempo de doença (p=0.92) ou grau de envolvimento cutâneo medido pelo PASI (p=0.59). A presença de áreas avasculares foi mais comum em indivíduos com psoríase que tinham envolvimento ungueal (p=0,047). CONCLUSÃO: Pacientes com psoríase têm menor densidade capilar e presença de capilares morfologicamente alterados em relação aos controles.